University-Industry Collaboration in Research and Development in Malaysian Universities (Journal of Business Management and Accounting, 2016)
The  focus  of  this  study  is  on  types  of  university-industry  collaboration  in  R&D projects  in  Malaysian  universities.  The  study  identified  the  benefits  derived  from University-Industry collaborations as it relates to performance of R&D project and the  characteristics  of  R&D  projects  that  encourage  industry  to  collaborate  with universities. It also makes recommendations towards increasing performance of R&D projects based on the data collected and analysed.  Exploratory approach was used in this study. This approach explored the collaboration types and how it contributed to R&D performance. Quantitative analysis was used by analysing questionnaire data. The reliability of the questionnaire items was tested. The respondents were people with experience in U-I collaborations. Data was analysed based on the five major elements in the theoretical framework. These are: benefits, performance, characters, practice and barrier. Based on the findings from the study, all of these five elements should be combined to ensure better R&D performance. The contribution of this study is the suggestions to universities in Malaysia and the Ministry of Higher Education (MOHE) to encourage increasing numbers of U-I collaborations.